Technological, pedagogical, content Knowledge (TPACK) research trends : A systematic literature review publish on 2010 to 2020: Research Article - Dewi, Novi Ratna; Rusilowati, Ani; Saptono, Sigit; Haryani, Sri; Wiyanto, Wiyanto; Ridlo, Saiful; Listiaji, Prasetyo; Atunnisa, Rifa' (Journal of Turkish Science Education, 2021)
The objective of the article review was to investigate research trends related to the TPACK topic, which is particularly useful for developing teacher learning abilities in line with the period of the industrial revolution 4.0, which uses a lot of technology integration in learning. This study is a TPACK systematic literature review out of 184 journal articles indexed by Scopus, published between 2010 and 2020. Findings show the countries that are the most TPACK research areas are Turkey and the United States. TPACK’s researchrelated articles are published mostly in technology-based education-oriented journals. There are still a few journals based on science education research that publish articles on TPACK. Topics about the components of knowledge in TPACK are the most researched, namely Knowledge, Technology, Content, and Pedagogical. The least studied is development and integration, which means that these two topics have not been of much interest to researchers in the last ten years. From several analyses in this literature review, we suggest various references and reference centers of TPACK in science education and formulate what topics need to be researched for further research.